Identifying the ranking of focal points in coordination games on the individual level - Robert J. Schmidt (University of Heidelberg, Department of Economics, 2019)
We propose a method to identify the ranking of focal points (Schelling, 1960) on the individual level. By contrast to conventional coordination, where subjects bet on only one alternative, subjects coordinate by the distribution of points. This allows them to invest in multiple alternatives and to weigh their choices. As a result, subjects not only reveal which alternative appears most focal to them, but the ranking of the available alternatives with regard to the degree of focality. In an experiment on the elicitation of social norms (Krupka and Weber, 2013), we compare the proposed mechanism with conventional coordination. The data confirms the theoretical predictions regarding coordination behavior and demonstrates that the proposed technique is suited to identify the heterogeneity of focal points on the individual level. Moreover, using Monte Carlo simulations, we find that the proposed mechanism identifies focal points on the group level significantly more efficiently than ordinary coordination. Finally, we point to the possibility to use the mechanism as a simple and direct tool to measure the degree of strategic uncertainty on the individual level.
urn:nbn:de:bsz:16-heidok-262344
Keywords: B41; C70; C91; 330; coordination; focal points; game theory; methodology; social norms